Pengaruh Media Tanam Dan Pupuk Organik Cair Terhadap Pertumbuhan Dan Produksi Tanaman Paria (Momordica charantia L.) - Maria Imakulata Nule; Ludgardis Ledheng; Maria Yustiningsih (JBIOEDRA: Jurnal Pendidikan Biologi, 2024)
Bitter Melon (Momordica charantia L.) is a fruit vegetable plant with numerous health benefits and the ability to treat various diseases. This study aims to determine the effects of growing media and liquid organic fertilizer on the growth and yield of bitter melon plants. The research was conducted on Jl. Basuki Rahmat, Kefamenanu Tengah Subdistrict, TTU Regency, from November to January 2021. The experimental method used was a Randomized Complete Block Design (RCBD) consisting of growing media and liquid organic fertilizer. The growing media included three treatments: 2 kg cow manure: 1 kg soil (A1), 2 kg rice husk: 1 kg soil (B2), and 2 kg goat manure: 1 kg soil (C3). The liquid organic fertilizer was applied at a rate of 5 ml/L for all treatments and replications. Data were analyzed using Analysis of Variance (ANOVA) with the SPSS 22.0 application. The results showed that the growing media and liquid organic fertilizer significantly affected plant height, number of leaves, number of productive branches, number of fruits, fruit length, and fruit diameter.